2019
DOI: 10.1093/mnras/stz3046
|View full text |Cite
|
Sign up to set email alerts
|

The very slow rotation of the magnetic O9.7 V star HD 54879

Abstract: The first FORS 2 spectropolarimetric observation of the longitudinal magnetic field of HD 54879 of the order of −600 G with a lower limit of the dipole strength of ∼ 2 kG dates back to 2014. Since then observations showed a gradual decrease of the absolute value of the mean longitudinal magnetic field. In the course of the most recent monitoring of HD 54879 using FORS 2 spectropolarimetric observations from 2017 October to 2018 February, a longitudinal magnetic field strength change from about −300 G down to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 32 publications
4
27
1
Order By: Relevance
“…A similar conclusion has been independently obtained by David-Uraz et al (2020). Notably, among the eleven magnetic O-type stars with known variation curves,for seven stars, HD 108, HD 37022 (= 1 Ori C), HD 54879, HD 148937, HD 191612, Tr 16-22, and NGC 1624-2, only one magnetic pole is visible throughout the rotation cycle (Shultz & Wade 2017;Petit et al 2008;Hubrig et al 2020;Wade et al 2012b;Donati et al 2006;Naze et al 2016, this work). This implies that, due to an unfavorable inclination of the rotation axis, a larger fraction of their surfaces can never be observed, leaving the structure of the field over the invisible surface only constrained by the assumption of a tilted centred dipole.…”
Section: Discussionsupporting
confidence: 86%
“…A similar conclusion has been independently obtained by David-Uraz et al (2020). Notably, among the eleven magnetic O-type stars with known variation curves,for seven stars, HD 108, HD 37022 (= 1 Ori C), HD 54879, HD 148937, HD 191612, Tr 16-22, and NGC 1624-2, only one magnetic pole is visible throughout the rotation cycle (Shultz & Wade 2017;Petit et al 2008;Hubrig et al 2020;Wade et al 2012b;Donati et al 2006;Naze et al 2016, this work). This implies that, due to an unfavorable inclination of the rotation axis, a larger fraction of their surfaces can never be observed, leaving the structure of the field over the invisible surface only constrained by the assumption of a tilted centred dipole.…”
Section: Discussionsupporting
confidence: 86%
“…The only exception, of course, is the field estimate obtained from the observations of February 17, 2018, for which we have measured a longitudinal field value of −250 ± 140 G, instead of −880 ± 120 G as reported by Hubrig et al (2019a). Hubrig et al (2019b) and Hubrig et al (2019c) also seem to come to conclusions similar to our own: namely that the reports of the sudden spectral and magnetic change and the large velocity variations are erroneous. However, they state that low S/N of the data is the culprit, and claim that this phenomenon is a reproducible, albeit spurious consequence of a problem with the reduction pipelines used.Their figure 8 shows a ∼ 300 Å region of two FORS2 observations obtained on 1 January, 2019 separated by just 25 minutes.…”
Section: Re-analysis Of the Fors2 Spectracontrasting
confidence: 70%
“…While we confirm the slow increase of the longitudinal field reported by Hubrig et al (2019a,b), we are unable to confirm the reported velocity variations, nor the sudden spectral and magnetic changes. Hubrig et al (2019b) also appear to conclude that the reports of the sudden spectral and magnetic change and the large velocity variations are erroneous. However, they ascribe this to a serious problem that they claim affects the FORS data reduction pipelines that they employed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…. M Hubrig et al (2020b) demonstrated that the O star HD 54879 rotates very slowly. According to FORS2 observations in 2014, its longitudinal magnetic field strength is G. Spectropolarimetric monitoring showed that from October 2017 until February 2018 the longitudinal field strength decreased from to G. New spectropolarimetric observations carried out over two months in 2018-2019 also showed slow field variations.…”
mentioning
confidence: 99%